Travaux de recherche du CIPEA sur les legumineuses fourrageres des hauts plateaux ethiopiens - Kahurananga, J. (1982)
Discusses ILCA's forage legume work in the Ethiopian highlands with particular reference to trifolium including germplasm collection. Presents data on DM yield, CP percentage and DM digestibility of four trifolium spp. and vicia villosa grown at Shola (Ethiopia) in 1981.